2017
DOI: 10.1007/s40309-017-0113-9
|View full text |Cite
|
Sign up to set email alerts
|

Disquieting uncertainty. Three glimpses into the future

Abstract: The article sketches three major realms -the realm of world order, the realm of work, and the realm of social policy -that will in all likelihood undergo fundamental change in the years and decades ahead, raising deeply unsettling questions about their future. The account is framed by the concept of global modernity, which, while not spelled out in detail, guides the presentation of data and other secondary materials in the aim to demonstrate connections between, and, at least to some extent, common roots of, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
5
0
2
Order By: Relevance
“…There are many forces that are placing a sense of urgency on the education system to transform itself for the future, which will drastically change the role of the teacher. Some of these forces include the Fourth Industrial Revolution (Schmidt, 2017;World Economic Forum, 2017), innovative pedagogies (Maldonado-Mahauad, Perez-Sanagustín, Kizilcec, Morales, & Munoz-Gama., 2018;Suárez, Specht, Prinsen, Kalz, & Ternier, 2018), information explosion due to the increasing use of the internet (Reyna, Hanham, & Meier, 2018), lifelong learning (Berry, 2018;Hinzen & Schmitt, 2016), artificial intelligence (Schmidt, 2017), and the move to open education resources (McGreal, 2017;Paskevicius & Hodgkinson-Williams, 2018;Redecker, 2017). This study identified necessary competencies of digital and online teachers who must adapt to the Internet and digital technologies of the future.…”
Section: Introductionmentioning
confidence: 99%
“…There are many forces that are placing a sense of urgency on the education system to transform itself for the future, which will drastically change the role of the teacher. Some of these forces include the Fourth Industrial Revolution (Schmidt, 2017;World Economic Forum, 2017), innovative pedagogies (Maldonado-Mahauad, Perez-Sanagustín, Kizilcec, Morales, & Munoz-Gama., 2018;Suárez, Specht, Prinsen, Kalz, & Ternier, 2018), information explosion due to the increasing use of the internet (Reyna, Hanham, & Meier, 2018), lifelong learning (Berry, 2018;Hinzen & Schmitt, 2016), artificial intelligence (Schmidt, 2017), and the move to open education resources (McGreal, 2017;Paskevicius & Hodgkinson-Williams, 2018;Redecker, 2017). This study identified necessary competencies of digital and online teachers who must adapt to the Internet and digital technologies of the future.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, however, the academic progress of futures and foresight as a field of study in Singapore is significantly underdeveloped relative to its resources. Indeed, only eleven full length journal articles have been published by authors originating from Singapore -excluding the authors of this article- in futures & foresight journals and specifically within the discipline in and of itself [7] (Andrews-Speed et al , 2014; Chan and Dee Von Chng, 2012; Cheah et al , 2019; Fan and Khng, 2014a, 2014b; Funk, 2015; Kuosa, 2011; Nair et al , 2014; Schmidt, 2017; Wen, 2013; Zahraei et al , 2020). Furthermore, none of these articles have attempted to advance neither the theories nor the methodologies of the field.…”
Section: Discussion and Contributionmentioning
confidence: 99%
“…One manuscript is an historical review of the field (Kuosa, 2011). Two manuscripts present conceptual arguments about present trends (Funk, 2015; Schmidt, 2017). Indeed, in a recent bibliographic review of the cumulative scholarly output in the futures and foresight field, universities in Singapore were not shown as a salient (highly cited) node of research vis-a-vis other institutions globally (Fergnani, 2019).…”
Section: Discussion and Contributionmentioning
confidence: 99%
“…DOI: 10.21666/muefd.1110034 Gelecek için eğitim sistemini hızlı bir dönüşüme zorlayan ve öğretmenin rolünü büyük ölçüde değiştiren pek çok faktör vardır. Dördüncü Sanayi Devrimi (Schmidt, 2017), yenilikçi pedagojiler (Maldonado-Mahauad vd., 2018;Suárez vd., 2018), internet kullanımının artması nedeniyle bilgi patlaması (Reyna vd., 2018), yaşam boyu öğrenme (Hinzen & Schmitt, 2016), yapay zeka (Schmidt, 2017) ve açık eğitim kaynaklarına geçiş (Paskevicius & Hodgkinson-Williams, 2018) bu faktörlerden sadece bazılarıdır. Bu faktörler ülkemizde çoğunlukla yükseköğretimde çevrimiçi derslerde hızlı bir dönüşüme neden olmuştur.…”
Section: Atıf Için: For Citationunclassified